2015
DOI: 10.1118/1.4917083
|View full text |Cite
|
Sign up to set email alerts
|

Impact of positional difference on the measurement of breast density using MRI

Abstract: Purpose: This study investigated the impact of arms/hands and body position on the measurement of breast density using MRI. Methods: Noncontrast-enhanced T1-weighted images were acquired from 32 healthy women. Each subject received four MR scans using different experimental settings, including a high resolution hands-up, a low resolution hands-up, a high resolution hands-down, and finally, another high resolution hands-up after repositioning. The breast segmentation was performed using a fully automatic chest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…We concluded that compression had a negligible effect in the thickness of the UAAL measurements. Other studies have indicated a high consistency in MRI BD measured at different field strength, image resolution, and patient positions [42]. …”
Section: Discussionmentioning
confidence: 98%
“…We concluded that compression had a negligible effect in the thickness of the UAAL measurements. Other studies have indicated a high consistency in MRI BD measured at different field strength, image resolution, and patient positions [42]. …”
Section: Discussionmentioning
confidence: 98%
“…Forty-one studies did not meet the selection inclusion criteria: no adequate breast density data (n = 20), qualitative analysis (n = 12), editorials (n = 4), conference abstracts (n = 3), post-mortem study (n = 1), and phantom study (n = 1). Finally, 38 studies attained the inclusion criteria [1,2,3,5,11,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57] and were included in the analysis as shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, 16 studies (41.03%) used non-contrast-enhanced T1-weighted [1,2,26,27,28,29,31,33,35,44,45,48,49,50,51,53], while in 12 studies (30.77%) non-contrast-enhanced images were integrated with contrast-enhanced images [25,36,37,38,39,40,41,42,43,44,47,49]. In terms of breast density segmentation/measurement, the majority of the studies (20 studies; 51.28%) used FCM clustering algorithm [1,2,11,25,26,27,28,29,31,32,33,34,35,36,37,38,39,40,41,42], while 7 studies (17.95%) used FCM and N3 algorithm [45,46,47,48,49,50,51], 4 studies (10.26%) interactive thresholding algorithm [3,5,52,53], 4 studies (10.26%) in-house customized software [29,53,54,55], one study (2.56%) manual software [57]; however, two studies did not provide the information [43,44].…”
Section: Resultsmentioning
confidence: 99%
“…Kopans has argued with respect to breast density determination: “Future investigations need to use 3D information,” and that “Radiologists can guesstimate the percentage of breast tissue that is dense, but they are still using 2D information to assess a 3D phenomenon.” To this end, volumetric measurement of breast density from intrinsically 3D imaging modalities is considered more accurate due to their scientific validity. Recently, 3D‐segmented magnetic resonance (MR) images have been used to assess breast density and appear to be robust to positioning issues and give reproducible results . However, MR imaging is relatively costly and requires specialized expertise to run and operate.…”
Section: Discussionmentioning
confidence: 99%
“…To this end, volumetric measurement of breast density from intrinsically 3D imaging modalities is considered more accurate due to their scientific validity. Recently, 3D-segmented magnetic resonance (MR) images have been used 45 to assess breast density and appear to be robust to positioning issues 46 and give reproducible results. 47 However, MR imaging is relatively costly and requires specialized expertise to run and operate.…”
Section: Discussionmentioning
confidence: 99%